Desenvolvimento de uma máquina supercondutora de fluxo aprisionado em fitas 2G empilhadas no rotor - Monteiro, Fernando Jorge (2020)
This thesis makes an in-depth investigation of the operating characteristics of a superconducting electrical machine that uses second generation tapes stacked in a spiral shape on the rotor. The operating principle of this machine depends on the interaction between the magnetic field generated in the conventional stator and the magnetic field trapped in the superconducting rotor. Thus, depending on the load, the machine can operate in synchronous or asynchronous regime. The stacks are used as an alternative to replace the bulks. The use of tapes reduces the size and weight of machines compared to those using bulks. In this context, three rotor core configurations have been proposed for the superconducting machine prototypes. One with a fiberglass core (N-G10), another with a high permeability magnetic steel core (N-MAG) and finally one with a fiber glass and magnetic steel core (N-G10MAG). The prototypes N-G10 and N-MAG have two superconducting tape stacks around the core, each one with nine layers, and the prototype N-G10MAG has three superconducting tape stacks around the core, each one with eighteen layers. These configurations were built and tested in a 77K liquid nitrogen bath. To perform these tests, two measurement tables and a cryostat were also developed. The experimental results agreed with the results obtained in a model developed with a finite elements program. The results demonstrated the magnetic flux trapping and magnetization of the superconducting stack in the rotor, being the weight was reduced by 36% and the torque increased by 60%, compared to the squirrel-cage induction machine, considering their respective operating temperatures.